Analisis Kinerja Guru berdasarkan Kompetensi dan Pengalaman Kerja (Studi pada Guru SMP Negeri di Kabupaten Bireuen) - Fakhrurazi, Fakhrurazi; Syaripuddin, Syaripuddin (Singkite Journal, 2023)
Performance analysis is part of the school management evaluation which is carried out from academic supervision activities. This continues to be done so that further action and policies can be taken. As it relates to the factors that affect the performance of school principals. So this analysis also evaluates the performance of school principals related to the influence of competence factors possessed and work experience. This research is in the form of a case study on the Principals of Public Junior High Schools in Bireuen Regency in 2022. This research uses a quantitative descriptive method and analysis techniques with multiple regression. Based on perception data through questionnaires, the results of the research conclusions are: 1). The performance level of Principals of public junior high schools in Bireuen Regency can be categorized as good with an average achievement of …%, as well as the level of competency is also in the good category although not optimal, namely reaching …% and from the aspect of work experience generally sufficient to become a leading professional school. 2) The results of the regression analysis show that there is a partial positive effect of competency and work experience factors on the performance of school principals. 3) Simultaneously the competence and work experience factors make a positive contribution to performance improvement, namely %.